Penerapan Optimasi Susunan Bahan Makanan untuk Ibu Hamil Penderita Kurang Energi Kronis (KEK) Menggunakan Algoritme Evolution Strategies - Firda Priatmayanti; Imam Cholissodin; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Maternal health during pregnancy, growth, birth, preparation of breastfeeding and infant growth is influenced by the addition of nutrients during pregnancy. The causes of Chronic Energy Deficiency or in Indonesia is Kurang Energi Kronis (KEK) in pregnant women is not sufficient to intake of energy and protein. The risk of pregnant women will experiencing KEK if the Upper Arm Circumference or in Indonesia is Lingkar Lengan Atas (LILA) have less than 23.5 cm. KEK in pregnant women can cause death indirectly and can cause Low Birth Weight or in Indonesia is Berat Badan Lahir Rendah (BBLR) in the children and BBLR can also cause to death and growing disordes of the child. Evolution Strategies used cycle of type (Î¼/r+ Î»). Chromosome representation used real-vector, recombination used intermediate recombination and mutation used self-adaption mechanism. Based on the results test, the best solution come from the population of 100 with an average fitness value of 20.34, the number of offspring of 30 with an average fitness value of 18.53, the number of generations of 100 with an average fitness value of 19.35. The solution given is the composition of food material to the nutritional nedds of pregnant women KEK for 7 days with anaverage of adequate nutritional needs of 78.5% and an average cost saving 35.81%.